Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1080/02841850701294560
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced FDG-PET/CT vs. spio-enhanced MRI vs. FDG-PET vs. CT in patients with liver metastases from colorectal cancer: a prospective study with intraoperative confirmation

Abstract: CT and SPIO-enhanced MR imaging are more sensitive but less specific than PET in the detection of LM. PET/CT can detect more patients with extrahepatic tumor than CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 35 publications
(48 reference statements)
6
88
0
11
Order By: Relevance
“…10 Rappeport et al reported that SPIONbased contrast agents, such as ferumoxides and ferucarbotrans, are specifically used for spleen and liver MR imaging because these agents are taken up by both macrophages in the spleen and Kupffer cells in the liver. 36,37 In the present study, we also observed accumulation of iron in both organs.…”
supporting
confidence: 68%
“…10 Rappeport et al reported that SPIONbased contrast agents, such as ferumoxides and ferucarbotrans, are specifically used for spleen and liver MR imaging because these agents are taken up by both macrophages in the spleen and Kupffer cells in the liver. 36,37 In the present study, we also observed accumulation of iron in both organs.…”
supporting
confidence: 68%
“…Compared to contrast-enhanced CT, MRI and especially SPIO-enhanced MRI seem to have a slightly superior sensitivity and specificity whereas PET clearly has an inferior sensitivity but superior specificity for CRLM; furthermore PET can also detect more patients with extrahepatic disease [33]. The lower costs and widespread availability however may favor the use of CT over MRI despite the radiation dose, especially if the accuracy of detection and characterization of focal liver lesions further improves with dynamic or at least multiphase CT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings also suggest that when PET/CT using low-dose CT for attenuation correction is performed, several liver metastases will not be found as low-dose CT used for attenuation correction will never find such small metastases. However, larger series are needed to confirm the results of this study (1), which makes for highly recommended reading.…”
mentioning
confidence: 87%